Estudos toxicológicos e anticâncer de uma fração rica em acetogeninas das sementes de Annona muricata L. - Silva, Antonio Adailson de Sousa (2019)
Cancer is a pathology that presents more than 100 different types and is defined as complex diseases of a mutational, proliferative character, of uncontrolled cellular growth, with the potential to invade the adjacent tissues and organs, being able to migrate to distant regions of the organism, characterizing the metastasis. Despite the current therapeutic armamentarium against cancer, several tumors still do not have adequate treatment and about 60% of the available drugs are of vegetable origin. In recent decades, anonaceous acetogenins have been prominent in the search for candidates for antitumor drugs because they have selective activity against tumor cells. This study aimed to evaluate the anticancer properties of an acetogenin rich fraction (FRA) isolated from Annona muricata L. seeds in experimental models in vitro and in vivo. A fraction rich in acetogenins (FRA) were prepared and tested in vitro (tumor line HCT-116) and in vivo (murine models). FRA presented selective cytotoxicity against HCT-116 cells as compared to non-tumor cell lines L929 by the MTT method, and erythrocytes treated with FRA showed no hemolysis (250 μg/mL). FRA-treated HCT-116 cells showed cycle changes, increasing the number of cells in the G0/G1 phase, resulting in apoptosis cell death, detected by the phosphatidylserine (annexin V) externalization assay. Corroborating with literature data, it may be suggested that the mechanism of action of FRA occurs mainly mitochondrial, since DNA damage and protein oxidation only appear after at least 12 hours of FRA treatment, and that pre-treatment with an antioxidant (GSH-OEt) has a potent protective effect on treated cells. In vivo models, FRA showed dose-dependent tumor growth inhibitory activity against Sarcoma 180 (model Mus musculus, albino, Swiss) and Walker 256 tumor (Rattus novergius model, Wistar). The histological parameters of the treated animals presented no difference between the groups, whereas biochemical and hematological parameters presented small alterations. Pontanto, data from these trials corroborate with data from the literature and FRA appears as a possible candidate for anticancer drug. However, further studies are needed for a better understanding of its mechanisms of action, pharmacokinetics and toxicity in the medium and long term.